Multiple harmonics reduction method for the integrated on-board battery charging system of hybrid electric vehicles - Kang, Ho Sung; Kim, Seok Min; Lee, Kyo Beum (IEEJ Journal of Industry Applications, 2020)
This paper proposes a multiple harmonics reduction method for the integrated on-board battery charging system of hybrid electric vehicles (REVs). The proposed system allows the starter generator and its drive inverter to operate as a battery charging system. The reconfiguration of the system results in the elimination of the conventional on-board charger (OBC), thereby reducing the system volume, weight, and manufacturing cost of REVs. In addition to the control method of the battery charging system, a harmonics compensation method is presented to improve the performance of the charging system. Different harmonics can be expressed as a unity variable in the synchronous reference frame by utilizing the phase sequence of the harmonics. The unified variable reduces the harmonic controller and simplifies the gain value selection. Simulation and experimental results verify the effectiveness of the integrated on-board battery charging system and its control method.
Keywords: Charging systems; Control methods; Harmonics compensation; Manufacturing cost; Multiple harmonics; On-board batteries; Starter generators; Synchronous reference frame; Harmonic Compensation Method; Hybrid Electric Vehicles; Integrated Charging System; On-Board Charger